Studying the effect of microwave heating on the digestion process and identification of proteins. Issue 3 (15th November 2016) - Devi, Shobha; Wu, Bo‐Hung; Chu, Pei‐Yu; Liu, Yue‐Pei; Wu, Hsin‐Lin; Ho, Yen‐Peng
Abstract : The impact of microwave irradiation on the in‐solution digestion processes and the detection limit of proteins are systematically studied. Kinetic processes of many peptides produced through the trypsin digestion of various proteins under microwave heating at 50°C were investigated with MALDI‐MS. This study also examines the detection limits and digestion completeness of individual proteins under microwave heating at 50°C and at different time intervals (1, 5 and 30 min) using LC‐MS. We conclude that if the peptides without missed cleavage dictate the detection limit, conventional digestion will lead to a better detection limit. The detection limit may not differ between the microwave and conventional heating if the peptides with missed cleavage sites and strong intensity are formed at the very early stage (i.e., less than 1 min) and are not further digested throughout the entire digestion process. The digestion of Escherichia coli lysate was compared under conventional and short time (microwave) conditions. The number of proteins identified under conventional heating exceeded that obtained from microwave heating over heating periods less than 5 min. The overall results show that the microwave‐assisted digestion is not complete. Although the sequence coverage might be better, the detection limit might be worse than that under conventional heating.